HUBUNGAN PATRON KLIEN TAUKE DAN PETANI SAWIT DI DESA SUNGAI LANGSAT KECAMATAN PANGEAN KABUPATEN KUANTAN SINGINGI - Mita Hariani; Nurhamlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Client Patron Relationship between Tauke and Farmer in Sungai Langsat Village, the tauke was the patron and the farmer was the client. The boss was usually someone who had large capital and also had responsibility for the crops of the farmers who were his clients. The purpose of this study was to determine the relationship between the tauke and oil palm farmers in Sungai Langsat Village, whether the patron-client requirements had been met and how the relationship between the tauke and oil palm farmers in Sungai Langsat Village was. In this study, the author used the patron-client theory proposed by James Scott which stated that the patron-client requirements consisted of personal relationships, loyalty relationships and reciprocal relationships. This study uses a descriptive qualitative approach. The research subjects of this study consisted of one key informant and six informants. The results obtained from this study were that the relationship between tauke and oil palm farmers in Sungai Langsat Village was a patron-client relationship. This could be seen from the relationship between the tauke and oil palm farmers in Sungai Langsat Village, there were personnel relationships, loyalty relationships and reciprocity relationships. There were three forms of relationship between the tauke and the oil palm farmers, which were used by researchers to determine the form of the patron client relationship between the tauke and oil palm farmers in Sungai Langsat Village, namely the form of exploitative relationships, forms of cooperative relationships and forms of symbiotic mutualism relationships. Keywords: Client Patron Relationship, Owner and Farmer, Palm Oil